Vitamin-Mediated Regulation of Intestinal Immunity - Kunisawa, Jun; Kiyono, Hiroshi (Frontiers in Immunology, 2013)
The intestine is exposed continuously to complex environments created by numerous injurious and beneficial non-self antigens. The unique mucosal immune system in the intestine maintains the immunologic homeostasis between the host and the external environment. Crosstalk between immunocompetent cells and endogenous (e.g., cytokines and chemokines) as well as exogenous factors (e.g., commensal bacteria and dietary materials) achieves the vast diversity of intestinal immune functions. In addition to their vital roles as nutrients, vitamins now also are known to have immunologically crucial functions, specifically in regulating host immune responses. In this review, we focus on the immunologic functions of vitamins in regulating intestinal immune responses and their roles in moderating the fine balance between physiologic and pathologic conditions of the intestine.